2008
DOI: 10.1111/j.1469-7998.2008.00478.x
|View full text |Cite
|
Sign up to set email alerts
|

Variations in body melanization impact desiccation resistance inDrosophila immigransfrom Western Himalayas

Abstract: Ectothermic species face problems of water balance under colder and drier climatic conditions in montane localities. We investigated five ecophysiological traits (body melanization, desiccation resistance, rate of water loss or gain and body size) in eight populations of Drosophila immigrans from an altitudinal gradient (600-2226 m) in the Western Himalayas. The traits showed bell-shaped variability patterns characteristic of quantitative traits. For body melanization, we observed high heritability (0.65) on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…Under this resistance hypothesis, melanic individuals have a selective advantage in more desiccating environments, like montane environments, than less or non-melanic individuals. Melanic Drosophila morphs were found in more-desiccating environments (higher altitudes) than non-melanic morphs (Parkash et al, 2008b(Parkash et al, , 2009, whereas darker abdominal pigmentation positively correlated strongly with altitude in sub-Saharan D. melanogaster populations (Pool and Aquadro, 2007). However, the altitudinal distribution of melanic H. maori differs from this pattern.…”
Section: Discussionmentioning
confidence: 49%
“…Under this resistance hypothesis, melanic individuals have a selective advantage in more desiccating environments, like montane environments, than less or non-melanic individuals. Melanic Drosophila morphs were found in more-desiccating environments (higher altitudes) than non-melanic morphs (Parkash et al, 2008b(Parkash et al, , 2009, whereas darker abdominal pigmentation positively correlated strongly with altitude in sub-Saharan D. melanogaster populations (Pool and Aquadro, 2007). However, the altitudinal distribution of melanic H. maori differs from this pattern.…”
Section: Discussionmentioning
confidence: 49%
“…For adaptations to drier habitats, the function of cuticular lipids in reducing cuticular water loss is well known in different insect taxa from deserts (Hadley, 1994). However, some studies have shown the role of melanisation in reducing cuticular water loss in Drosophila species (Parkash et al, 2008b;Parkash et al, 2008c). Associations between pigmentation and desiccation resistance were initially proposed by Kalmus (Kalmus, 1941).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in body melanisation have been shown to affect cuticular permeability in some Drosophila species (Parkash et al, 2008b;Parkash et al, 2008c). According to the melanisation-desiccation hypothesis, darker flies of D. melanogaster are abundant in cooler uplands while lighter flies are predominant in foothills (Parkash et al, 2008c).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations